2007
DOI: 10.1136/ard.2007.077552
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anti-tumour necrosis factor   treatment on the antibody response to influenza vaccination

Abstract: The antibody response to influenza vaccination in patients treated with anti-TNF is only modestly impaired. The proportion of patients that achieves a protective titre is not significantly diminished by the use of TNF blocking therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
90
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(103 citation statements)
references
References 15 publications
(14 reference statements)
10
90
0
3
Order By: Relevance
“…However, when patients are receiving immunosuppressive therapies with combined thiopurines and anti-TNF agents, serologic responses to vaccines are impaired ( 22,23,(43)(44)(45)(46)(47)(48)(49)(50)(51). Nonetheless, even a blunted vaccination response is thought to be of benefi t ( 52 ) and thus recommendations for infl uenza vaccination with inactivated vaccine continue to be broadly applicable to all patients, regardless of immunosuppression status ( 13,53 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…However, when patients are receiving immunosuppressive therapies with combined thiopurines and anti-TNF agents, serologic responses to vaccines are impaired ( 22,23,(43)(44)(45)(46)(47)(48)(49)(50)(51). Nonetheless, even a blunted vaccination response is thought to be of benefi t ( 52 ) and thus recommendations for infl uenza vaccination with inactivated vaccine continue to be broadly applicable to all patients, regardless of immunosuppression status ( 13,53 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Numerous authors state similar efficiency of vaccination for RA patients and healthy volunteers, without any significant influence of DMARD's or biological therapy on the humoral response (Elkayam 2006;Rahier et al 2010). A few recent studies reported a mild or severe impairment of the humoral response after administration of biological therapy in patients suffering from RA (Gelinck et al 2008;van Assen et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…87,88 For example, some studies have suggested that patients on TNF inhibitors may have a slightly decreased immune response to influenza vaccine. [89][90][91] Specific data for patients with IBD are very scarce. Some authors have evaluated the serological response to influenza vaccine in patients with IBD and observed that those receiving anti-TNF therapy were less likely to be seroprotected.…”
Section: What Factors Affect the Efficacy Of Hbv Vaccination In Ibd Pmentioning
confidence: 99%